Disparate results between proliferation rates of surgically excised prostate tumors and an in vitro bioassay using sera from a positive randomized controlled trial. (April 2015) - Azrad, M; Vollmer, RT; Madden, J; Polascik, TJ; Snyder, DC; Ruffin, MT; Moul, JW; Brenner, D; He, X; Demark-Wahnefried, W
Abstract: In vitro bioassay has been used extensively to test the effects of culturing cancer cells in sera from humans participating in dietary interventions, i.e, studies of modified intake of nutrients for the purpose of reducing cancer risk or progression. It has been hypothesized that cell proliferation rates determined by the in vitro bioassay indicate whether modification of dietary intake could decrease cancer cell growth in vivo. It has been suggested, however, that the in vitro bioassay may not correlate with tumor cell proliferation rates in prostate cancer. We investigated the concordance of cell proliferation rates from surgically excised prostate tumor tissue with the in vitro bioassay using sera from matched patients. We used samples from an earlier randomized clinical trial that showed that supplementation with flaxseed significantly inhibited prostate cancer cell proliferation rates in vivo as indicated by Ki67 staining in tumor specimens. Proliferation rates of LNCaP, DU145 and PC3 cell lines cultured in 10% human sera from participants in the flaxseed trial were determined using 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. Spearman's Rho correlation coefficients (ρ) indicated no association between Ki67 staining in prostate tumors and the in vitro bioassay for the three cell lines. These disparate findings suggest that the in vitro bioassay may not provide an accurate assessment of the environment in vivo.